+0

# Solve the equation.

+3
394
4
+253

Solve the equation.

e2x − 9ex + 8 = 0

e6x + 5e3x − 14 = 0

x 2 3 x −  4( 3 x) = 0

sally1  Jul 9, 2014

#3
+18829
+24

x 2 3 x −  4( 3 x) = 0    ?

$$\\x^2 3^x-4(3^x)=0 \\ 3^x ( x^2-4 ) =0 \\ 3^x ( x-2 ) ( x+2 ) =0\\\\ \underbrace{3^x}_{=0} \times( \underbrace{x-2}_{=0} ) \times( \underbrace{x+2}_{=0} ) =0 \\\\ \boxed{3^x=0} \quad | \quad \ln{} \\\\ \ln{(3^x)} = \ln{(0)} \\ x\ln{(3)} = \ln{(0)} \\ x= { \ln{(0)} \over \ln{(3)} } } \quad | \quad \ln{(0)} \mbox{ no solution !}\\\\ \boxed{x-2=0} \quad \Rightarrow \quad \boxed{x=x_1=2}\\\\ \boxed{x+2=0} \quad \Rightarrow \quad \boxed{x=x_2=-2}$$

heureka  Jul 10, 2014
Sort:

#1
+18829
+24

e2x − 9ex + 8 = 0  ?

$$\\e^{2x}=e^xe^x \quad | \quad \mbox{ set }\quad \boxed{z=e^x}\\ z^2 -9z +8=0\\ \underbrace{1}_{a=1}z^2 \underbrace{-9}_{b=-9}z \underbrace{+8}_{c=8} =0\\ \boxed{z_{1,2}= { -b\pm\sqrt{b^2-4ac} \over 2a } }\\\\ z_{1,2}= { 9\pm\sqrt{81-4*1*8} \over 2*1 } \\\\ z_{1,2}= { 9\pm\sqrt{81-32} \over 2} \\\\ z_{1,2}= { 9\pm7\over 2} \\\\ \boxed{z_1= 8 \quad z_2 = 1} \\\\ e^x=z \quad | \quad \ln\\\\ \ln{(e^x)}=\ln{(z)}\\\\ x\ln{(e)}=\ln{(z)} \quad | \quad \ln{(e)}= 1 \quad !\\\\ \boxed{x=\ln{(z)}} \\\\$$

$$\\x=x_1=\ln{(8)}=2.07944154168\\ x=x_2=\ln{(1)}=0\\ \boxed{x_1=2.07944154168 \qquad x_2=0}$$

heureka  Jul 10, 2014
#2
+18829
+24

e6x + 5e3x − 14 = 0 ?

$$\\e^{6x}=e^{3x}e^{3x} \quad | \quad \mbox{ set }\quad \boxed{z=e^{3x}}\\ z^2 +5z -14=0\\ \underbrace{1}_{a=1}z^2 \underbrace{+5}_{b=5}z \underbrace{-14}_{c=-14} =0\\ \boxed{z_{1,2}= { -b\pm\sqrt{b^2-4ac} \over 2a } }\\\\ z_{1,2}= { -5\pm\sqrt{25-4*1*(-14)} \over 2*1 } \\\\ z_{1,2}= { -5\pm\sqrt{25+56} \over 2} \\\\ z_{1,2}= { -5\pm9\over 2} \\\\ \boxed{z_1= 2 \quad z_2 = -7} \\\\ e^{3x}=z \quad | \quad \ln\\\\ \ln{(e^{3x})}=\ln{(z)}\\\\ 3x\ln{(e)}=\ln{(z)} \quad | \quad \ln{(e)}= 1 \quad !\\\\ \boxed{x={1\over 3}\ln{(z)}} \\\\$$

$$\\x=x_1={ \ln{(2)}\over 3} } =0.23104906019\\ x=x_2={ \ln{(-7)}\over 3} } = \mbox{no solution !}\\\\ \boxed{x=0.23104906019}$$

heureka  Jul 10, 2014
#3
+18829
+24

x 2 3 x −  4( 3 x) = 0    ?

$$\\x^2 3^x-4(3^x)=0 \\ 3^x ( x^2-4 ) =0 \\ 3^x ( x-2 ) ( x+2 ) =0\\\\ \underbrace{3^x}_{=0} \times( \underbrace{x-2}_{=0} ) \times( \underbrace{x+2}_{=0} ) =0 \\\\ \boxed{3^x=0} \quad | \quad \ln{} \\\\ \ln{(3^x)} = \ln{(0)} \\ x\ln{(3)} = \ln{(0)} \\ x= { \ln{(0)} \over \ln{(3)} } } \quad | \quad \ln{(0)} \mbox{ no solution !}\\\\ \boxed{x-2=0} \quad \Rightarrow \quad \boxed{x=x_1=2}\\\\ \boxed{x+2=0} \quad \Rightarrow \quad \boxed{x=x_2=-2}$$

heureka  Jul 10, 2014
#4
+91451
+6

Really nice work Heureka!

I'd give you more points if I could.

Melody  Jul 11, 2014

### 6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details